Legal aspects of land administration digitalization: international experience and prospects for Kazakhstan (VERITAS LEGIS JOURNAL, 2025)
This article presents an analysis of the digitalization of land administration in Kazakhstan, including legal aspects and global practices that could be integrated into this country. Today, the trend toward globalization is expanding, reinforcing the need for stable land resource management. Kazakhstan faces barriers such as non-digitized information, low digital literacy among the rural population, and uneven legal reforms. The high importance of sharing international experience and creating an institutional environment is highlighted by practices such as the Estonian E-Land model and Singapore's geoinformation technologies. The solution to these problems is presented through a set of measures, including improving digital literacy, developing telecommunications infrastructure, and harmonizing land legislation with international standards. The effectiveness of the proposed measures is assessed through the flexibility of global practices, including legal mechanisms, in the context of Kazakhstan's socio-economic specifics. The data obtained will contribute to sustainable development and improvement of the quality of life of the population.
Keywords: digitalization, land administration, international experience, land relations, land policy, land legislation, digital legal framework.